2016
DOI: 10.1051/kmae/2016029
|View full text |Cite
|
Sign up to set email alerts
|

Do fishing education programs effectively transfer ‘catch-and-release’ best practices to youth anglers yielding measurable improvements in fish condition and survival?

Abstract: -There is growing interest in educating anglers on catch-and-release (C&R) best practices, yet there is little information on whether angler education programs yield measurable improvements in fish condition and survival. As such, we conducted a study focused on mixed-gender youth groups (aged 8-10) and contrasted three levels of training intervention. Treatment 1 training had no mention of C&R best practices. Treatments 2 and 3 trainings involved visual aids to illustrate best practices, while Treatment 3 add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…An example would be the Marine Conservation Society's "Good Fish Guide," which recommends more sustainable sources of seafood to consumers (www.mcsuk.org. Anglers are often aware of and comply with the best C&R practices available (Delle-Palme et al, 2016;Nguyen et al, 2013) and have been shown to socially sanction anglers who do not follow best practices (Guckian et al, 2019). A "Good Bait Guide" could be created and circulated throughout angling networks, to instil a voluntary set of "best bait practices" into the angling community, potentially reducing the use of threatened species such as river lamprey as bait and bait sources at risk from pathogen transmission (Vollmar et al, 2015).…”
Section: Attitudes Regarding Lamprey Conservationmentioning
confidence: 99%
“…An example would be the Marine Conservation Society's "Good Fish Guide," which recommends more sustainable sources of seafood to consumers (www.mcsuk.org. Anglers are often aware of and comply with the best C&R practices available (Delle-Palme et al, 2016;Nguyen et al, 2013) and have been shown to socially sanction anglers who do not follow best practices (Guckian et al, 2019). A "Good Bait Guide" could be created and circulated throughout angling networks, to instil a voluntary set of "best bait practices" into the angling community, potentially reducing the use of threatened species such as river lamprey as bait and bait sources at risk from pathogen transmission (Vollmar et al, 2015).…”
Section: Attitudes Regarding Lamprey Conservationmentioning
confidence: 99%
“…Some of the sampled dead fish were noted to have angler inflicted injuries caused by hook removal. Research by Palme et al (2016) observed an improvement in the condition of anglercaught fish after anglers attended education programs. Clubs should therefore be encouraged to hold seminars promoting best practices aimed at reducing fish mortality.…”
Section: Discussionmentioning
confidence: 98%
“…For this purpose, three anglers with the same level of experience in recreational fishing (10-20 years) were selected from Elazığ Amateur and Sportive Angling Club. They were also educated and trained about how to handle the angled fish for assessing short-term mortality and how to make a record of different information that included fish capture time, hooking location (upper jaw, lower jaw, both upper and lower jaw), bleeding (non-bleeding, stage-1 minor bleeding, and stage-2 heavy bleeding), fish total length (cm), and fish weight (g) (Atessahin, 2019;Broadhurst et al, 2012;Delle Palme et al, 2016).…”
Section: Fishing Eventsmentioning
confidence: 99%